Serunya Bermain Tanpa Teknologi - Eka Setya Ayu Prasasty; Anindita Nadine K; Budi Erisaputri; Tomi Kurniawan; Monica Nelly Agustine; Kiki Dian Setiawan (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
As technology develops, traditional games have begun to be marginalized by modern games, such as video games, Play Station, online games available on computers, cellphones and laptops, and other modern games. Children's play patterns are starting to shift to play patterns at home. Traditional games are one method that can be used so that people do not feel bored while doing gaming activities. Based on the campaign activities carried out by the implementing team, namely Communication Science students at Semarang University, by incorporating traditional games into their daily lives, equipped with adequate facilities in the community environment, they can slowly grow their interest in playing and ultimately minimize the use of gadgets in their daily lives.